2000
DOI: 10.1145/362426.362472
|View full text |Cite
|
Sign up to set email alerts
|

The case for profile-directed selection of garbage collectors

Abstract: Many garbage-collected systems use a single garbage collection algorithm across all applications. It has long been known that this can produce poor performance on applications for which that collector is not well suited. In some systems, such as those that execute stand-alone compiled executables, an appropriate collector for each application can be selected from a pool of available collectors and tuned by using profile information. In a study of 20 benchmarks and several collectors, compiled with the Marmot o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…We refer to any point at which the bestperforming GC system changes as a switch point. These results support the findings of others [4,16,42], that no single collection system enables the best performance across benchmarks; moreover no single system performs best across heap sizes for a single benchmark/input pair.…”
Section: Application-specific Gcsupporting
confidence: 89%
See 3 more Smart Citations
“…We refer to any point at which the bestperforming GC system changes as a switch point. These results support the findings of others [4,16,42], that no single collection system enables the best performance across benchmarks; moreover no single system performs best across heap sizes for a single benchmark/input pair.…”
Section: Application-specific Gcsupporting
confidence: 89%
“…However, many researchers have shown that there is no single combination of a collector and an allocator that enables the best performance for all applications, on all hardware, and given all resource constraints [4,16,42]. Figure 1 confirms these findings.…”
Section: Application-specific Gcmentioning
confidence: 55%
See 2 more Smart Citations
“…It is a well-established fact that the relative performance of different GC algorithms is dependent on the characteristics of the application being executed [17,28,35] particularly at smaller heap sizes.…”
Section: Relative Gc Performance Is Application Dependentmentioning
confidence: 99%